Building Resilience in Global Tourism: A Theoretical and Empirical Analysis of Indicators for Sustainable Development - Erol, İsmail; Dogru, Tarik; Öztel, Ahmet; Bilgihan, Anil; Peker, İskender; Neuhofer, Irem Onder (Wiley, 2026)
The primary perspective of this study is the global tourism industry (GTI) as an interconnected supply chain network, encompassing both tourism firms (e.g., hotels, airlines, and operators) and destinations (e.g., local communities and ecosystems). This industry-level focus allows for analyzing resilience indicators that bridge firm-specific capabilities with destination-wide vulnerabilities, rather than isolating one over the other. Using a mixed-method approach, this research conceptualizes resilience through various management theories. First, it identifies critical resilience indicators across institutional, societal, economic, and ecological dimensions. Second, these indicators are analyzed with a novel Spherical Fuzzy Interpretive Structural Modeling and Cross-Impact Matrix Multiplication Applied to Classification framework, utilizing expert opinions to uncover complex interdependencies among indicators. The findings of this study highlight that effective government policies, robust incentive mechanisms, advanced digital infrastructure, dynamic capabilities, and ecologically sustainable tourism practices are key drivers of resilience. However, socioeconomic impacts, tourist satisfaction, and price competitiveness emerge as highly dependent outcomes influenced by these drivers. This study also introduces the Adaptive Global-Local Interaction Theory, a new framework that integrates global influences with local realities to enhance tourism resilience. By offering a comprehensive framework and practical guidelines, this research equips policymakers and stakeholders with actionable strategies to bolster the industry's capacity to anticipate, adapt to, and recover from crises, promoting sustainable development amidst volatile global conditions.
Keywords: Fuzzy Modeling; Global Tourism Industry; Resilience Indicators; Sustainability; Theory-Based Approach